1. 3x - 2y = 0 => y = 3/2x
4x + 2y = 14<=> 4x + 2*(3/2x) = 14<=> 7x = 14<=> x = 2 & y = 3
2.3p + q = 7=> q = 7 - 3p
2p - 2q = -6<=> 2p - 2*(7-3p) = -6<=> 2p - 14 + 6p = -6<=> 8p = -6 + 14 = 8<=> p = 1 & q = 4
3.3x - 2y = 1=> x = (1+2y)/3
8x + 3y = 2<=> 8*(1+2y)/3 + 3y = 2<=> 8*(1+2y)/3 - 2 = -3y<=> 3*(8*(1+2y)/3 - 2) = -3*(3y)<=> 8*(1+2y) - 6 = -9y<=> 8 + 16y - 6 = -9y<=> 2 = -25y<=> y = -2/25 & x = 7/25
Each year it will gain $10 so it will take 50 years.
1,000 × .02 = 20
1,000 ÷ 20 = 50
Answer:
i pick my answer as 3
Step-by-step explanation:
7-4=3
Answer:True
Step-by-step explanation:Empirical generalisation is the relationship between two variables that has been observed over a long period of time, science tries to show the interactions taking place between empirical Generalisation and theory,empirical Generalizations can also be seen as a pattern that repeats over different circumstances. Empirical Generalizations can also be said to be a reasoning from large example to basic conclusions which can be represented mathematically graphically or symbolically.
Answer:
x = 2 is a solution
x = 0 is an extraneous solution
(Option 2)
Step-by-step explanation:
4/x = (3x + 2)/x²
4x² = 3x² + 2x
x² - 2x = 0
x(x - 2) = 0
x = 0, x = 2
Verification:
4/x = (3x + 2)/x²
At x = 2
4/2 = [3(2) + 2]/2²
2 = 8/4
2 = 2
At x = 0
4/0 = [3(0) + 2]/0²
Is undefined